Coopération scientifique et débat sur les « sciences sociales africaines » au CODESRIA - Aboubacar Abdoulaye Barro (Les éditions de la Maison des sciences de l'Homme, 2010)
This main goal of this paper is to show that despite CODESRIA's (Council for the Development of Social Science Research in Africa) dependency on funding from donor agencies in the West, original scholarship is being produced by the organization. The scarcity of financial resources, the limitation of academic freedom in African universities, and the strong presence of a Codesria intellectual Diaspora in the West, do not prevent the organization from legitimizing its discourse in Africa. This "counter-hegemonic" position has created numerous tensions among scholars in the West, Africanists in particular, and within Codesria itself. Since Codesria's establishment, the many controversies surrounding its intellectuals' mission to build "African social Sciences" can be explained by their critical attitude towards Western scholars, but also by the limitations of such an agenda in globalised context.